PCR identification of lactic acid bacteria populations in corn silage inoculated with lyophilised or activated Lactobacillus buchneri - Maia dos Santos, Ana Paula; Santos, Edson Mauro; Silva de Oliveira, Juliana; Garcia Leal de Araújo, Gherman; de Moura Zanine, Anderson; Martins Araújo Pinho, Ricardo; Costa do Nascimento, Thiago Vinícius; Fernandes Perazzo, Alexandre; Ferreira, Daniele de Jesus; da Silva Macedo, Alberto Jefferson; de Sousa Santos, Francisco Naysson (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
This study aimed to evaluate the effect of inoculation with lyophilised and/or activated Lactobacillus buchneri on lactic acid bacteria populations in corn silage. Experimental treatments consisted of corn silage without additives or silage with the inoculants of L. buchneri (1 x 105 cfu/g) applied according to the manufacturer’s recommendations (1 g/tonne fodder) in the forms of the lyophilised inoculant and pre-activated inoculant. Purified isolates from corn silage with and without the inoculant were identified, and 93% of the isolates corresponded to the lactic acid bacteria of the species Lactobacillus plantarum. Among the isolates, no bacteria of the species L. buchneri were detected. The application of lyophilised or activated L. buchneri improved the microbiological profile and reduced ethanol production in corn silage, even without being identified among the isolates captured 70 days after ensilage. Highlights: Lactic acid bacteria showed greater development at 7 days of fermentation. Lactobacillus plantarum predominated at 70 days, representing 93% of the total LAB population. Lactobacillus buchneri improved its microbiological profile with decreased ethanol production.